The Impact of Glucagon-Like Peptide 1 Receptor Agonists on Bone Metabolism and Its Possible Mechanisms in Osteoporosis Treatment - Xie, Baocheng; Chen, Shichun; Xu, Yongxiang; Han, Weichao; Hu, Runkai; Chen, Minyi; Zhang, Yusheng; Ding, Shaobo (Frontiers in Pharmacology, 2021)
The effect of anti-diabetic drugs on bone metabolism is receiving increasing attention due to the close correlation between type 2 diabetes mellitus (T2DM) and osteoporosis. T2DM would lead to bone fragility, high risk of fracture, poor bone healing and other skeletal related events. In addition, some hypoglycemic drugs for T2DM may have notable detrimental skeletal effects. Thus, the appropriate therapeutic strategy for T2DM should not only be effective in glucose control but also in minimising complications of bone metabolism. Glucagon-like peptide-1 receptor agonists (GLP-1RAs) are novel and promising drug for the treatment of T2DM. GLP-1RAs may play an anti-osteoporosis role by promoting bone formation and inhibiting bone absorption. However, the specific impact of GLP-1RA on fracture risk and osteoporosis have not been unambiguously defined. This review summarizes the current research findings by which GLP-1RAs treatment of diabetic osteoporosis, postmenopausal osteoporosis and glucocorticoid-induced osteoporosis(GIOP) and describe possible mechanisms, such as GLP-1R/MAPK signaling pathway, GLP-1R /PI3K/AKT signaling pathway and Wnt /β-catenin pathway, that are associated with GLP-1RAs and osteoporosis. The specific processes and related molecular mechanisms of different types of GLP-1RAs on bone metabolism need to be further explored and clarified.